Relationship between Organizational Justice and Effectiveness of Human Resource Management Practices: A Mediating Role of Demographic Information in Greater Irbid Municipality (GIM) in North Region | of Hashemite Kingdom of Jordan (HKJ) - Ajlouni, Sultan; Ajlouni, Wajdee; Al-Ajlouni, Wisal (Dirasat: Human and Social Sciences, 2021)
The purpose of this study is to investigate the impact of organizational justice on effectiveness of human resources management (HRM) practices in Greater Irbid Municipality (GIM) in the north region of Hashemite Kingdom of Jordan (HKJ). The population of the study consisted of 440 employees in all. The study was conducted during the month of July, 2018. The data required for the study was collected through a well-structured questionnaire; and the sample consisted of 102 employees. The main findings of the study showed that organizational justice (OJ), distributive justice and interactional justice dimensions registered the highest mean scores. Recruitment and selection recorded the highest mean scores of effectiveness of human resource management. There was a significant correlation between OJ and effectiveness of HRM practices. Future research can be undertaken to find the relationship and impact between OJ and effectiveness of HRM practices in non-governmental organizations and quasi-governmental bodies.